PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA (SURVEI PADA PENGGUNA JASA PENGGUNA SISTEM APLIKASI INAPORTNET YANG TERDAFTAR DI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS I BANJARMASIN) - Ferra Maryana; Rakhmi Ridhawati; Riski Evi Astuti (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This research aimed to give empirical evidences about the effect of system and information quality to user satification of Inaportnet which listed in Office of First Class Harbour and Port Authority Banjarmasin. The independent variable was system quality and information quality. The dependent variable was user satisfication. The population in this study was 150 employees of 241 companies who used Inaportnet. The data collected from the output of questionnaires which gived to the respondents. The samples technique used purposive sampling with 150 employees as respondent. The research gived empirical evidences that system quality and information quality had effect to user satification partial and simoultantly.